Pharmacokinetics and neurotropic effects of cyclo-L-prolylglycine and its modified analogues - S. S. Boyko; V. P. Zherdev; K. N. Koliasnikova (LLC "Publisher OKI", 2022)
The review presents the results of studies on the pharmacokinetics, metabolism, and bioavailability of new neurotropic dipeptide cyclo-Lprolilglycine (CPG) and their pharmacological activity. It was shown that the pharmacologically active metabolite of the nootropic drug noopept cyclo-Lprolilglycine (CPG) is an endogenous dipeptide, it is a fragment of the terminal Tripeptide of the insulin-like nerve growth factor IGF-1. Much attention is paid both in Russia and abroad to the development of modified CPG analogues with improved pharmacokinetic properties, enzymatically more stable, better penetrating the BBB, and highly effective when used in micromolar doses. CPG shows neuroprotective activity in ischemic-hypoxic and other brain injuries, in addition, it has a complex of other pharmacological effects and therefore CPG can be considered not only as a potential drug, but also as a basic structure for the development of new neurotropic drugs - analogs of CPG with improved pharmacokinetic properties, greater enzymatic resistance and higher bioavailability for the central nervous system.